Socio-Economic Factors in Determining the Female Labour Force Participation in Sri Lanka - Vasana, J. L. A.; Siriwardhane, D. R. J. (My University, 2021)
This study aims to explore the socio-economic factors that shape female labour force participation in Sri Lanka. Accordingly, secondary data from the Central Bank of Sri Lanka and the World Bank were employed to explore major socio-economic factors using the ARDL model. The results of the study conclude that there is an impact of economic growth on the female labour force participation both in the short and long run, also enhancement in economic performance would create a negative impact on the female labour force participation both in the short and long run. Further, it was found that the size of the urban population and female unemployment also has a negative impact on female labour force participation in the country. However, the fertility rate of women creates a positive impact on female labour force participation. The nature of the relationship between economic growth and female labour force participation was further examined using a co-integration test performed with the ARDL boundary test approach. Results revealed a significant inverted U-shaped relationship which is different to extant literature. It portrayed how at the first phase of economic growth of the country, female labour force participation increased and then began to decrease following a certain level of economic growth.
Keywords: ARDL model, economic growth, female labour force participation